Hydrolysis of lignocellulosic material of carob pulp in Batch, SSF and NSSF processes for ethanol production - Raposo, Sara (2014)
The progress of technologies for fuel ethanol production is a priority, because this biofuel is one of the most important resources used as renewable energy sources.